Integrating interactive media for social connectedness at urban public parks in sustainable smart cities: a systematic review - Ying, Lum Huey; Abd. Shukor, Shureen Faris; Ibrahim, Roziya; Mohd Yunos, Mohd Yazid (Human Resource Management Academic Research Society, 2024)
Youth park usage is low due to high levels of sedentary behaviour and a lack of attractive park elements. Such high sedentary behavior is causing deterioration of youths’ well-being as more youths are losing their social connectedness. Therefore, there is a need to develop an urban public park for promoting health and well-being for youths. This study is part of a larger study in promoting youth physical activities by integrating interactive media technology at urban public park in Hong Kong. The purpose of this study is to identify urban public park features which could attract physical activities among youths. This article presents the results of a systematic literature review synthesis process on urban public park for youths. Results found nature, facilities, and programs are critical for attracting physical activities among youths. In addition, the parks could improve youth’s well-being when their physical activities are supported by interactive media technologies experiences which are best integrated with engaging social connections. This study contributes in developing a proposed model for a Youth-connected Interactive Media Park. The proposed model is expected to lead to developing public urban parks that are attractive to youths hence could activate outdoor physical activities among youths. Future studies are recommended to investigate how tapping into smart city’s technological interventions could make social connectedness through preferred park features by youths for their physical activities.